Peer Influence and Self-Efficacy on College Interest: The Mediating Role of School Environment in Vocational High School Students - Estu Niana Syamiya; Aniek Widiarti Widiarti; Heni Cahya Ramdani; Noviyanti Hasanah (Universitas Negeri Padang, 2026)
This study aims to analyze the prediction of higher education intentions among vocational students: assessing the mediating role of the school environment on self-efficacy and peer relationships. The research method used is quantitative and uses path analysis. The study population was grade XII students of SMK Negeri 3 Tangerang City, with a sample of 202 respondents selected through probability sampling techniques. Data collection was conducted using a questionnaire. The results show that peers have an effect on their interest in continuing their studies. The results show that self-efficacy affects the interest in continuing college. The academic setting significantly predicts further education interest. This indicates confirming that the indirect path from peer surroundings to college intention is statistically insignificant. That self-efficacy does not have an indirect effect on the interest in continuing college through the school environment. Therefore, peers and self-efficacy are important factors in shaping interest in continuing their studies, while the role of the school environment in this context is not strong enough to exert a meaningful influence. These findings emphasize the importance of strengthening students' social interactions and self-confidence in increasing educational aspirations. This new research adds the school environment as a mediating variable, which provides new insights into solving the problem of students' inclination towards post-secondary education.